2021
DOI: 10.1038/s41598-021-86147-9
|View full text |Cite
|
Sign up to set email alerts
|

Chondrogenic and BMP-4 primings confer osteogenesis potential to human cord blood mesenchymal stromal cells delivered with biphasic calcium phosphate ceramics

Abstract: Bone marrow mesenchymal stem/stromal cells (BMSCs) show great promise for bone repair, however they are isolated by an invasive bone marrow harvest and their regenerative potential decreases with age. Conversely, cord blood can be collected non-invasively after birth and contains MSCs (CBMSCs) that can be stored for future use. However, whether CBMSCs can replace BMSCs targeting bone repair is unknown. This study evaluates the in vitro osteogenic potential of unprimed, osteogenically primed, or chondrogenicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Cell therapies can be combined with CaPs to enhance their osteogenic potential [16][17][18]. Biomaterial constructs act as delivery vehicles, provide regenerative cues, and act as structural scaffolds to permit the influx of host cells and regeneration of tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Cell therapies can be combined with CaPs to enhance their osteogenic potential [16][17][18]. Biomaterial constructs act as delivery vehicles, provide regenerative cues, and act as structural scaffolds to permit the influx of host cells and regeneration of tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Kern et al reported that CB-MSCs could not differentiate toward adipocytes, similar findings were also reported for PL-MSCs (238). Other investigators, besides confirming the low adipogenic potential of CB-MSC (258), have reported higher osteogenic (247,259) and chondrogenic potential (257,260). Differences in identical genetic background perinatal MSC sources have also been described, with strikingly inconsistent results reported from AM-MSCs (216).…”
Section: Tri-lineage Differentiation Potentialmentioning
confidence: 72%
“…They can be isolated from several adult and fetal tissues, including bone marrow and umbilical cord blood (CB) [8,9]. MSCs are well-known to contribute to tissue repair in chondrogenic and osteogenic damaged tissues [10] and reduce apoptosis in damaged cells supporting tissue regeneration [11][12][13], but the most clinically relevant therapeutic effect relies on their immunomodulatory properties. Indeed, MSCs interact with each cellular component of the immune system.…”
Section: Introductionmentioning
confidence: 99%